Geometry Evaluation of Mine Road Based on AASHTO 73 to PT Semen Padang’s Hauling Devices Fuel Needs - Ghina Qatrunnada; Guskarnali Guskarnali; Haslen Oktarianty (MINERAL, 2020)
This research examines the geometry of haul roads found at Front Mining 242 towards Crusher VI PT Semen Padang, West Sumatra. This research is based on the results of previous research that there are slope and width that is not in accordance with AASHTO standards on several segments in the mining location. The research also examined the fuel consumption of Komatsu HD785 and Caterpillar 777D haulage devices. This research was conducted by taking data of road geometry using GPS Geodetic and roll meter. Haul roads are divided into several segments with a spacing of about 100 m each. Fuel consumption is calculated based on total resistance received by haulage devices. The evaluation results of the haul road from Crusher VI to Front Mining 242 are the width of the haul road for the two lines in the straight line is 24.1 m, the average width of the actual road is 19.58 m. The width of the haul road for the two lanes on the bend is 24.88 m, the average road width on the actual bend is 21.63 m. Bend radius according to standard 22.81 m, in actual conditions Points M17 and M36 do not meet the standard. The slope of the road according to the standard is 10%, the actual condition averages 13.31%. The amount of cross slope according to the standard is 48.2 cm, the actual condition averages 0 cm. The use of Komatsu HD785 fuel is greater than 15.97 l /rity compared to Caterpillar 777D with a total of 14.98 l/rity. The use of Komatsu HD785 fuel on the recommended road with bend radius 22.81 m to 10.58 l/rity and at the radius of bend 33.35 m to 9,90 l/rity. The use of Caterpillar 777D fuel on the recommended road with bend radius 22.81 m to 8.92 l/rity and at the radius of bend 33.35 m to 8.35 l/rity